The decisive role of molecular pathology in presumed somatic metastases of type II testicular germ cell tumors: report of 2 cases - Mariëtte E. G. Kranendonk; Wenzel M. Hackeng; G. Johan A. Offerhaus; Folkert H. M. Morsink; Geertruida N. Jonges; Gerard Groenewegen; Pieter-Jaap Krijtenburg; Heinz-Josef Klümpen; Wendy W. J. de Leng; Leendert H. J. Looijenga; Lodewijk A. A. Brosens (BMC, 2020)
Abstract Background Molecular diagnostics can be decisive in the differential diagnosis between a somatic metastasis of type II testicular germ cell tumor (TGCT) or a second primary carcinoma. This is in line with recent recommendations from the International Society of Urological Pathology, based on an international survey which showed that molecular testing is currently only performed by a minority of urological pathologists. Case presentations This case report illustrates the necessity of molecular testing in two patients with a history of type II TGCT and a metastatic (retro) peritoneal carcinoma years later. The genetic hallmark of type II TGCT, chromosome 12p gain, was studied by fluorescence in situ hybridization and whole genome methylation profiling in case 1, and by single nucleotide polymorphism (SNP)-array in case 2. Next generation sequencing (NGS) was used to further explore clonality between the primary TGCT and peritoneal metastasis in case 2. In case 1, chromosome 12p gain was found in the primary type II TGCT and in the acinar cell carcinoma of the metastatic malignancy. In case 2, SNP array showed 12p gain in the epithelial component of the primary teratomatous TGCT but not in the peritoneal adenocarcinoma. Furthermore, NGS showed no mutations in the primary teratomatous TGCT but a KRAS and GNAS mutation in the peritoneal adenocarcinoma, suggestive of an appendicular origin. Conclusions Without the molecular data, both cases would have been regarded as a metastatic TGCT with development of somatic-type malignancy, which appeared a wrong diagnosis for case 2. These cases demonstrate the importance of molecular methods as an adjunct in today's pathology practice.